2021
DOI: 10.1155/2021/3442277
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Jujube (Ziziphus jujuba Mill.) Response to Heat Stress

Abstract: Heat stress (HS) is a common stress influencing the growth and reproduction of plant species. Jujube (Ziziphus jujuba Mill.) is an economically important tree with strong abiotic stress resistance, but the molecular mechanism of its response to HS remains elusive. In this study, we subjected seedlings of Z. jujuba cultivar “Hqing1-HR” to HS (45°C) for 0, 1, 3, 5, and 7 days, respectively, and collected the leaf samples (HR0, HR1, HR3, HR5, and HR7) accordingly. Fifteen cDNA libraries from leaves were construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Jujubes are widely planted by Chinese over long history especially in Xinjiang province. Enriched with vitamin C, carbohydrates, organic acids, amino acids and minerals content [3],jujubes provide health bene ts such as antitumor, hepatoprotective, anti-in ammatory and neuroprotective effects [9].In traditional Chinese medicine, jujubes are believed as supplement of blood. To celebrate festivals, Chinese cook jujubes to make porridge, pastries and zongzi [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jujubes are widely planted by Chinese over long history especially in Xinjiang province. Enriched with vitamin C, carbohydrates, organic acids, amino acids and minerals content [3],jujubes provide health bene ts such as antitumor, hepatoprotective, anti-in ammatory and neuroprotective effects [9].In traditional Chinese medicine, jujubes are believed as supplement of blood. To celebrate festivals, Chinese cook jujubes to make porridge, pastries and zongzi [10].…”
Section: Discussionmentioning
confidence: 99%
“…However, FBs as batteries, buckyballs and needles may retain and result in impaction due to special physical or chemical properties [2].Impaction of FBs develops ulcerations and perforation, or even lethal conditions. Jujubes, harvest in fall, are major agricultural crops in Xinjiang, mainland of China [3].Jujube pits, spindle-shaped objects with sharp ends, hard to pass through intestinal tract during peristalsis and discharge with feces when impaction happens. Unlike adults, children are not able to distinguish edible objects from non-edible objects and have poor swallowing coordination [4].…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome analysis of leaves at the jujube ( Ziziphus jujuba Mill.) seedling stage revealed that multiple HSPs such as HSP17, HSP18, HSP21, HSP22, HSP23, HSP26, HSP70, HSP83, HSP90, HSF30, and HSC-2 were upregulated [ 37 ]. These results suggested that Hsfs and Hsps were crucial in plants under heat stress.…”
Section: Genes Involved In Rna and Protein Stabilitymentioning
confidence: 99%
“…Based on the literature, bioactive compounds extracted from Z. jujuba have miscellaneous activities such as therapeutic effects on the nervous system, cardiovascular system, and gastrointestinal tract, improving the quality of sleep, as well as antioxidant, anti-inflammatory, and anti-cancer properties, and strong effects on blood purification ( 11 ). Furthermore, Z. jujuba can treat typhoid fever, diabetes, diarrhea, skin infections, anxiety, obesity, pharyngitis, bronchitis, anemia, and insomnia ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%